(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1864)
This article describes the different strata of gravel, sand and clay that was exposed at Kinleith burn during the excavation of ground for construction. An unknown bronze implement and several small bones were uncovered during the excavation and were exhibited at the Society on the day. The author discusses similar bronze tools found in Ireland and Switzerland. He goes on to speculate that the item found at Kinleith may have been used for shaving. A chemical analysis of the bronze artefact had a lower than average proportion of tin.